The Basic Requirements of the Multi-Syllabus Syllabus - BELOUAHEM, Riad (Journal of Human Sciences, 2009)
This article aims at providing a description of the basic principles and the fundamental requirements of the different syllabuses in the field of foreign language learning/ teaching. It is also intended to give an illustration of the kind of framework for a foreign language syllabus teachers should like to see implemented. It goes without saying that a successful course which is more eagerly looked for is the one which combines all essential aspects: structure, function, situation, topic, skills in an integrated and coherent way.